Foundry in the Late Bronze Age Baiões/Santa Luzia Cultural Group : some reflections starting from a new metallic mould for unifacial palstaves - Senna-Martinez, João Carlos (2020)
During the last quarter of a century, progress on the understanding of metallurgical practices of the Baiões / Santa Luzia cultural group of Central Portugal produced results that allowed us to better understand and characterize a fundamental cultural group of the Iberian Late Bronze Age (LBA). However, the study of the foundry moulds lacks a convenient interpretive synthesis. The discovery of a new exemplar of metallic mould for single-faceted palstaves – one of the types that characterize Central Portugal LBA metallurgy – creates the opportunity to, starting with its archaeometallurgical characterization, produce an overview of Baiões / Santa Luzia moulds and foundry procedures, namely for the palstaves moulds that, until now, are mostly known in the area of this cultural group.